Transient ocular surface non-perfusion during cataract phacoemulsification surgery - Yijun Hu; Wei Qi; Baoyi Liu; Honghua Yu (BMC Ophthalmology, 2020)
Abstract Background Complete non-perfusion of the anterior segment vasculature during cataract phacoemulsification surgery is rarely reported. Case presentation We present two cases of transient ocular surface non-perfusion (TOSN) during cataract phacoemulsification surgery. The TOSN happened during intraocular lens (IOL) implantation with complete vanish of blood flow in the conjunctival, episcleral and limbal vessels. Reperfusion started within 30 s and part of the blood supply of the conjunctiva and episclera was restored within 2 min. However, the blood flow in the limbal vessels was not restored until 5 min later. The postoperative examination of both eyes was normal. These two rare cases are the TOSN during cataract surgery. We speculated that the significantly increased intraocular pressure during IOL implantation might be the cause of this rare phenomenon. Conclusion Non-perfusion of the ocular structures may occur if the IOP peak during IOL injection exceeds the perfusion pressure of the anterior vasculature.